Principal change leadership competencies and teacher attitudes toward change: the mediating effects of teacher change beliefs - Tai, Mei Kin; Abdull Kareem, Omar; Nordin, Mohamad Sahari; Khuan, Wai Bing (Taylor & FRancis, 2017)
This study investigates the relationship between Principal Change Leadership Competencies, Teacher Change Beliefs and Teacher Attitudes toward Change. A total of 936 teachers from 47 High Performing Secondary Schools in Malaysia completed the survey. Structural equation modelling was applied to test the models. Firstly, the results showed that Principal Change Leadership Competencies was significantly related to Teacher Change Beliefs and implied that if school principals equipped themselves with sufficient Principal Change Leadership Competencies, Teacher Change Beliefs can certainly be enhanced. Secondly, Teacher Change Beliefs was significantly related to Teacher Attitudes toward Change whereby the stronger the Teacher Change Beliefs, the greater the enhancement of Teacher Attitudes toward Change. Thirdly, Teacher Change Beliefs was indeed a total mediator in the relationship of Principal Change Leadership Competencies and Teacher Attitudes toward Change. Put simply, via Teacher Change Beliefs, the impact of Principal Change Leadership Competencies on Teacher Attitudes toward Change was relatively strong as Teacher Change Beliefs greatly facilitated the influence of Principal Change Leadership Competencies on Teacher Attitudes toward Change. Thus, in-depth enhancing Teacher Change Beliefs is one of the effective ways to increase the likelihood of teachers to embrace change. Fourthly, Principal Change Leadership Competencies was more influential than teachers’ self-influence in enhancing Teacher Attitudes toward Change. Therefore, concerted effort must be given to prioritize the continuous development of principal change leadership in effective change management. The study encourages a fresh look at change leadership development and ultimately alters the traditional approach of school principals in managing change.